Television Journalism, Journalistic Sources and Social Network Communication in TV News - Morales Blanco, Estefany (2016)
This paper is aimed to understand the relation between Television Journalism, journalistic sources and social network communication. Also, it explains how television news production benefits of the contact with journalistic sources, which have changed since the use of virtual platforms such as Facebook and Twitter. This is a non experimental, applicative, descriptive, correlative and multivariable study. The sample consisted in thirty journalists from television news program “ATV Noticias” (Andina de Radiodifusion Company, Lima, Peru). The research concluded that the frequent use of Internet and Social Networks impacted television news programs. This happens during television production process: themes selection, contact with journalistic sources and reporters work, until the outline and the feedback generated by the Social Networks.